Climate Change Science: A Modern Synthesis - Farmer, G. Thomas; Cook, John (Springer, 2013)
This textbook, Climate Change Science : A Modern Synthesis, Volume I: The Physical Climate , is intended for the introductory college science student who perhaps has not had a science course since secondary or preparatory school. It is also intended to serve as a more advanced textbook for students who have had a basic science course in astronomy , geology , biology , physics , or chemistry and who want to better understand Earth ’s climate , how Earth’s climate has developed, what affects it, and how it may change in the future . However, it presumes no background in any of the sciences. Basic scienti fi c concepts are introduced and explained as they become necessary for understanding the current topic. It constitutes Volume I of a twotextbook treatment of climate change science designed for a 1-year introductory science course. This volume treats the physical aspects of climate change science and is intended for a one-semester or one-quarter introductory science course. Volume II emphasizes the historical aspects of climate change and Earth science. Each volume is a stand-alone treatment of climate change science, Volume I emphasizing the physical and chemical portions of the science while Volume II emphasizes the evolution and historical aspects of the science. Each volume presents arguments of climate change and global warming skeptics and deniers and the scientific evidence that refutes or supports each argument. The last two chapters in this text discuss denial in the face of overwhelming scienti fi c evidence. Neither volume assumes a prior college or preparatory course in science or mathematics but they do assume an interest in the world around us. The necessary science is introduced in the context of the evolving subject matter in the text. Mathematics is kept to a minimum in each volume and an understanding of preparatory-school algebra should be suf fi cient to tackle the mathematics of most climate science concepts contained herein. Additional readings for each chapter contain mathematical material where appropriate.